Individualized luteal phase support. Issue 3 (June 2019) - Lawrenz, Barbara; Coughlan, Carol; Fatemi, Human M.
Abstract : Purpose of review: The aim of this review is to summarize the different aspects of luteal phase deficiency in IVF treatment and the possibilities of individualized luteal phase support. Recent findings: After the application of human chorionic gonadotrophin (hCG) for final oocyte maturation, the vaginal route for progesterone administration is sufficient to maintain an adequate luteal phase support. New data point toward the possibility of oral medication; however, those data have yet to be confirmed in larger studies. Luteolysis after gonadotropinrealzing hormone (GnRH) agonist trigger is patient specific and not always severe. According to the progesterone level, individualized low dosages of hCG can be applied as luteal phase support without the risk of ovarian hyperstimulation syndrome (OHSS) development. Summary: It is the task of the reproductive medicine specialist to individualize luteal phase support according to the patient's specific characteristics, needs and desires and the type of treatment performed. The greatest indication for individualization of the luteal phase is following GnRH agonist trigger in high responder patients in order to tailor luteal phase support to the patient-specific pattern of luteolysis and minimize the risk of causing OHSS with unnecessary high hCG dosages.